Pematahan Dormansi Dan Perkecambahan Benih Kopi Robusta (Coffea Canephora) Dengan KNO3 dan Air Kelapa - Mulkiah, Lika Malika; Hidayat, Odang; Hadi, Roni Assafaat (OrchidAgro, 2023)
Conducted in the experimental garden of the Faculty of Agriculture, Winaya Mukti University, Tanjungsari, Sumedang, which is located at an altitude of 850 meters above sea level, this study aims to find out how various concentrations of KNO3 and coconut water affect the dormancy breaking of robusta coffee seed germination in nurseries. The experiment started in June 2021 and lasted until August 2021. This experiment used a randomized group factorial pattern (RBD) repeated twice. The first factor in the experiment was the concentration of KNO3 (K) with four levels, namely k0 = 0%, k1 = 0.5%, k2 = 1%, and k3 = 1.5%. The second factor is the concentration of coconut water (P) with four levels, namely p0 = 0%, p1 = 30%, p2 = 60%, and p3 = 90%. The results showed that treatment with KNO3 and coconut water had an impact on germination at 36 HST. The independent effect showed a significant effect on germination at 39 HST, seedling height at 56 HST, wet weight and dry weight at 56 HST. In contrast, the independent effect showed no significant effect on germination at 42 HST, growth rate at 35 to 56 HST, normal sprouts at 56 HST.